Analisis Karakteristik Bagi Anak Autisme di SKHN 02 Kota Serang : Penelitian - Lulu Hayati; Yahdinil Firda Nadirah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to assess the condition of children with autism, identify the difficulties they face in communication and interaction, and find out the types of special services provided for children with autism at SKh 02 in Serang city. The study employs a qualitative approach using a case study method. The participants in this study consist of a child with autism and several key informants, including teachers and parents. Data were collected through observation, interviews, and documentation techniques. The observation results reveal various challenges, difficulties, and obstacles faced by children with autism.